Plato on maritime trade. Elements for an interpretation of the Anthropocene - Montoya , María Del Pilar (2023)
Through the study of some passages that Plato devotes to the analysis of the psychological, political and economicrepercussions of the economic activities of the empirical cities, we intend to show that Plato’s economic thought, fundamentally in relation to the import and export trade carried out by sea, offers elements of inestimable value for thinking about the relationship between the dynamics of consumption and production promoted by globalization and the attitude of human beings towards the Earth and the consequences that arise from it.